2010
DOI: 10.1007/s00415-010-5603-7
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide in managing impulse control disorders in Parkinson’s disease

Abstract: Impulse control disorders (ICDs) are a set of behaviours that take place in a subgroup of patients with Parkinson's disease (PD). Although reduction or switch of dopamine agonists or decrease of levodopa are the common treatment, this does not always improve the compulsive behaviour. Zonisamide (ZNS) has proved effective for motor symptoms in PD and it may be also useful in the field of ICDs. The aim of our study is to evaluate the safety and efficacy of ZNS in PD patients with ICDs who did not improve followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…However, a post hoc analysis of participants in the DOMINION study (728 patients using amantadine, 2357 without amantadine use) determined that amantadine was positively associated with a diagnosis of any ICD [143], and so use of amantadine is currently controversial. In a small, open-label study, 15 patients with ICDs were treated with zonisamide, a sulphonamide analogue, (starting dose 25 mg/day, titrated as tolerated to 200 mg/ day) and a marked reduction in the severity of impulsive behaviors and global impulsiveness was found without a significant change in motor function [144]. There are published case reports and retrospective reviews describing successful treatment of ICDs with donepezil [145], quetiapine [146], clozapine [147,148], valproate [149] (risk of motor deterioration), topiramate [150], naltrexone [151], finasteride [152], cyproterone acetate [153] (for hypersexuality in a patient with PDD), and variable results with SSRIs [149,154,155], lowdose risperidone [156,157], and olanzapine [149] (risk of motor deterioration with risperidone and olanzapine).…”
Section: Management Icdsmentioning
confidence: 99%
“…However, a post hoc analysis of participants in the DOMINION study (728 patients using amantadine, 2357 without amantadine use) determined that amantadine was positively associated with a diagnosis of any ICD [143], and so use of amantadine is currently controversial. In a small, open-label study, 15 patients with ICDs were treated with zonisamide, a sulphonamide analogue, (starting dose 25 mg/day, titrated as tolerated to 200 mg/ day) and a marked reduction in the severity of impulsive behaviors and global impulsiveness was found without a significant change in motor function [144]. There are published case reports and retrospective reviews describing successful treatment of ICDs with donepezil [145], quetiapine [146], clozapine [147,148], valproate [149] (risk of motor deterioration), topiramate [150], naltrexone [151], finasteride [152], cyproterone acetate [153] (for hypersexuality in a patient with PDD), and variable results with SSRIs [149,154,155], lowdose risperidone [156,157], and olanzapine [149] (risk of motor deterioration with risperidone and olanzapine).…”
Section: Management Icdsmentioning
confidence: 99%
“…In addition, zonisamide, an antiepileptic drug with CA inhibitory activity, has been reported to increase extracellular and intracellular dopamine concentration in rodents (Okada et al 1995;Tominaga et al 2001). Furthermore, zonisamide is used to treat impulsivity control disorder in Parkinson's disease (Bermejo et al 2010). Besides the dopaminergic system, the noradrenergic system has been reported to be involved in the anticonvulsant activities of CA inhibitors (Gray and Rauh 1974;Torchiana et al 1973).…”
Section: Discussionmentioning
confidence: 98%
“…Acetazolamide (AZ), an inhibitor of CA, has been used as an anticonvulsant since 1952 (Bergstom et al 1952), and the anticonvulsant activity of CA inhibitors, including AZ and methazolamide (MZ), has been reported to involve noradrenergic mechanisms (Gray and Rauh 1974;Torchiana et al 1973). Zonisamide, another CA inhibitor and anticonvulsant, stimulates Ca 2+ -evoked monoamine release (Kawata et al 1999;Tominaga et al 2001) and has been shown to be beneficial for patients with Parkinson's disease (Bermejo et al 2010;Murata 2010). In addition, CA has been shown to affect the switching of gamma-aminobutyric acid (GABA) A receptors between excitation and inhibition (Ting et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…ZNS has been suggested to improve several impulse control disorders such as binge eating disorder and alcohol intake. Our group [Bermejo and Velasco, 2008] evaluated the safety and efficacy of ZNS in a small group of patients with impulse control disorders and PD who did not improve following either a reduction of or switch to L-DOPA or dopamine agonists. Results suggested that this drug might also play a role when these disorders are associated with PD.…”
Section: Neuroprotectionmentioning
confidence: 99%
“…In addition to its effects on patients with epilepsy, ZNS has been suggested to have beneficial efficacy in various neurological and psychiatric diseases. Migraine [Bermejo and Dorado, in press], neuropathic pain [Guay, 2003], essential tremor , impulse control disorders [Bermejo and Velasco, 2008] and Parkinson's disease (PD) are possible uses of this drug. Similar to ZNS, other antiepileptic drugs have been proposed to treat different pathologies and the name 'neuromodulators' has been proposed for them [Bazil, 2004].…”
Section: Introductionmentioning
confidence: 99%